Insight into genomic organization of pathogenic coronaviruses, SARS-CoV-2: Implication for emergence of new variants, laboratory diagnosis and treatment options - Bedada, Fikru B.; Gorfu, Gezahegn; Teng, Shaolei; Neita, Marguerite E. (Frontiers in Molecular Medicine, 2022)
SARS-CoV-2 is a novel zoonotic positive-sense RNA virus belonging to the genus beta coronaviruses (CoVs) in the Coronaviridae family. It is the causative agent for the outbreak of the disease, COVID-19. It is the third CoV causing pneumonia around the world in the past two decades. The gravity of the global pandemic caused by SARS CoV-2 is so enormous that new cases and deaths have been peaking at a pace difficult to manage by wealthy nations. Furthermore, the emergence of new genetic variants has exacerbated the challenge. Since genetic alterations (mutations) are known to occur in viral infections leading to emergence of new variants, information harnessed from SARS-CoV-2 genomic organization is indispensable. Indeed, this is evident by the emergence of several new variants of SARS-CoV-2 including the Alpha (UK), Beta (South Africa), Gamma (Brazil), Delta (India), Lambda (Peru) and recently Omicron (South Africa) and its divergent sublingeages (BA.1, BA.2 and BA.3) with BA.2 currently on the rise potentially overtaking Omicron and prolonging the COVID pandemic. Given that the magnitude of the challenge posed by SARS-CoV-2 is fueled by the emergence of new genetic variants, information extracted from the genomic structure of SARS-CoV-2 is of paramount importance in variant identification (molecular diagnosis and molecular pathology), monitoring (molecular epidemiology) as well as research towards development of specific vaccines, monoclonal antibodies, and antiviral drugs. Therefore, this review article is focused on current understanding of the genomic organization of SARS-CoV-2, emergence of genetic alterations (mutation) causing divergence with features unique to SARS-CoV-2 relative to SARS-CoV and MERS-CoV.